Gambaran Faktor-Faktor Penyebab Stunting pada Balita di Wilayah Kerja Puskesmas Sibela Kota Surakarta - Siti Mutmainah; Riyani Wulandari (Yayasan Literasi Sains Indonesia, 2023)
Indonesia is the second rank with the highest stunting rate in the Southeast Asia region. Stunting in Central Java reached 20.9%. Meanwhile, Surakarta City is the second highest rank for stunting in Central Java, namely 29.38%. Sibela Health Center is one of the Health Centers with the highest stunting prevalence in Surakarta. Stunting can be caused by maternal factors, toddler factors as well as social, economic, and environmental factors. The purpose of this study was to determine the factors that cause stunting in toddlers at Sibela Health Center in Surakarta City. The method of this study is the Cross- Sectional Survey method collecting data on one population. The results showed that stunting in toddlers at Sibela Health Center in Surakarta city was caused namely energy, and protein on toddlers had not been fulfilled (64.2%), including income under the region's minimum wage (76.9%) and most toddlers are exposed to cigarette smoke (50.7%).